Vertical Line Extension Decisions in a Competitive Market with Consumers’ Need for Product Uniqueness - Jie Wang; Qin Su; Canyou Wang (Discrete Dynamics in Nature and Society)
One important reason for offering customized products is to satisfy consumers’ need for product uniqueness. In this paper, we take consumers’ unique preferences into account to examine how firms make decisions on vertical line extensions with introducing a customized product. This study develops the consumer’s utility function, which captures consumers’ behavioural and emotional factors, and the results show that the high-quality firm always introduces an upward extension without uniqueness sensitivity. However, introducing a downward extension may be more profitable especially when consumers have the high unique ness sensitivity. We also find that the upward extension of the high-quality firm does not intensify competition with the low-quality firm, but its downward extension will intensify the competition between two firms, whether with or without unique preferences. We also analyse the low-quality firm’s extension decisions when it faces a high-end competitor and find that the low-quality firm may change from introducing a downward extension to introducing an upward extension when intrafirm quality differentiation is small.